Immunogene expression analysis in betanodavirus infected-Senegalese sole using an OpenArray® platform. - Gémez-Mata, Juan; Labella Vera, Alejandro Manuel; Bandín Matos, Isabel; Borrego-García, Juan José; García-Rosado, Esther (Elsevier, 2021)
The transcriptomic response of Senegalese sole (Solea senegalensis) triggered by two betanodaviruses with different virulence to that fish species has been assessed using an OpenArray® platform based on TaqMan™ quantitative PCR. The transcription of 112 genes per sample has been evaluated at two sampling times in two organs (head kidney and eye/brain-pooled samples). Those genes were involved in several roles or pathways, such as viral recognition, regulation of type I (IFN-1)-dependent immune responses, JAK-STAT cascade, interferon stimulated genes, protein ubiquitination, virus responsive genes, complement system, inflammatory response, other immune system effectors, regulation of T-cell proliferation, and proteolysis and apoptosis. The highly virulent isolate, wSs160.3, a wild type reassortant containing a RGNNV-type RNA1 and a SJNNV-type RNA2 segments, induced the expression of a higher number of genes in both tested organs than the moderately virulent strain, a recombinant harbouring mutations in the protruding domain of the capsid protein. The number of differentially expressed genes was higher 2 days after the infection with the wild type isolate than at 3 days post-inoculation. The wild type isolate also elicited an exacerbated interferon 1 response, which, instead of protecting sole against the infection, increases the disease severity by the induction of apoptosis and inflammation-derived immunopathology, although inflammation seems to be modulated by the complement system. Furthermore, results derived from this study suggest a potential important role for some genes with high expression after infection with the highly virulent virus, such as rtp3, sacs and isg15. On the other hand, the infection with the mutant does not induce immune response, probably due to an altered recognition by the host, which is supported by a different viral recognition pathway, involving myd88 and tbkbp1.
Keywords: Peces-Virus; Solea senegalensis; Reassortant nervous necrosis virus; Immune response; OpenArray®; Differentially expressed genes (DEGs)